Data analytics and intuitive Intelligence: ensuring ‘VARCS’ data in business - Subiah, Manj (Henry Stewart Talks, 2022)
Integrated intelligence, Valid, Authentic, Reliable, Current, Sufficient (VARCS), Volatility, Uncertainty, Complexity, Ambiguity (VUCA), Priming effect, Halo effect, Bias, Illusion